Antagonist Test of Gliocladium sp. against Fusarium sp. Cause of Wilt Disease in Shallot Plants In Vitro - Sarayar, Dea; Umboh, Stella Deiby; Siahaan, Parluhutan (JURNAL BIOS LOGOS, 2025)
This study aims to analyze the morphological characteristics of the fungus Gliocladium sp., measure its inhibition against the growth of the fungus Fusarium sp. causing wilt disease in shallot plants (Allium ascalonicum L), and examine its antagonistic mechanism in vitro. This research method includes exploration and sampling, sterilization of tools and materials, making PDA media, isolation, purification, and identification of morphological characteristics and measurement of antagonistic fungal inhibition. The antagonist test uses the dual culture method, and data analysis with a completely randomized design (CRD) and ANOVA test followed by the Honestly Significant Difference (HSD) Test at the 5% significance level. The results showed that Gliocladium sp. was able to inhibit the growth of Fusarium sp. with a percentage inhibition of 25.63% and spore viability of 66.52%. Antagonistic mechanisms observed include competition for space and nutrients, antibiosis, lysis, and mycoparasitism.